Chapter 11 Multilingual teacher identity in the Emirates Implications for language policy and education - Calafato, Raees (Taylor & Francis, 2022)
A growing number of countries are implementing school initiatives aimed at developing students' knowledge of multiple languages to help them thrive in a globalized world. Research indicates that learning languages can be made more effective if teachers draw on their own and their students' entire language repertoires during lessons, yet few studies have systematically investigated the extent to which language teachers are willing and able to do this. This chapter reports the findings from a mixed-methods study on secondary school teachers of Arabic, English, and French based in the UAE that explored their teaching practices using an ecological perspective. Drawing upon data collected via unstructured interviews, the study's findings revealed common themes among the participants vis-à-vis their ability and willingness to draw on their and their students' multilingualism as a pedagogical resource. The chapter concludes by offering recommendations for how schools and policymakers can implement specific measures to help teachers and students fully realize their multilingual potential.